Assessment of performance of metabentonite and metazeolite-based geopolymers with fly ash sand replacement - Aygormez, Yurdakul (ELSEVIER SCI LTD, 2021)
Geopolymer is a sustainable product that supports environmental protection and creates an alternative solution to Portland Cement. Investigation of the use of different binders in geopolymer production is potential research in this area. Bentonite and zeolite, which can be obtained naturally and at a low cost, were calcined at 750 degrees C and used as binders in this study. Calcined bentonite (metabentonite (MB)) and calcined zeolite (metazeolite (MZ)) were replaced with each other in four different percentages (25%, 50%, 75%, and 100% by weight). In addition, the study was carried out by replacing fly ash (FA) with standard sand in five different percentages (15%, 30%, 45%, 60%, and 75% by weight). Ten geopolymer series were subjected to flexural-compressive strength and ultrasonic pulse velocity (UPV) tests at 7, 28, and 90 days. To see the effects after the durability conditions, 450 cycles of freeze-thaw test and the high-temperature test (200, 500, and 800 degrees C) were also applied to geopolymer mortars. Along with the durability tests, varying UPV, weight, and strength results were also found. SEM analyzes were also applied to see the changes with durability tests. The results showed that metazeolite had higher results due to its higher Si/Al ratio and more stable zeolitic structure. Also, the use of fly ash up to 30% increased the pozzolanic feature which reflected positively on the results. When all effects were evaluated together, it showed that the prepared geopolymer samples were resistant to durability effects.
Keywords: Geopolymer; Metabentonite; Metazeolite; Fly ash; High-temperature test; Freeze-thaw test; MECHANICAL-PROPERTIES; CONCRETE; METAKAOLIN; CEMENT; BEHAVIOR; FIBER; BENTONITE; STRENGTH; DURABILITY; COMPOSITES; Construction & Building Technology; Engineering; Materials Science